PET high-pressure-resistant material for aerosol bottle and preparation method of PET high-pressure-resistant material

By adding specific ratios of nylon, composite reinforcement and corrosion-resistant agent to the PET material, the problems of poor heat resistance, pressure resistance and corrosion resistance of PET materials are solved, and PET materials with high pressure resistance, high heat resistance and high corrosion resistance are achieved.

CN119613926APending Publication Date: 2025-03-14FOSHAN XUJIE PACKAGING TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411893386.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The heat resistance, pressure resistance and corrosion resistance of the PET materials prepared in the prior art are poor.

Method used

The composite reinforcement was prepared by terephthalic acid, 1,4-cyclohexanedimethanol, isosorbate, pimelic acid and triphenyl phosphate using the ratio of 60-80 parts of PET resin, 20-25 parts of nylon, 5-10 parts of composite reinforcement, 4-9 parts of anticorrosion agent, 7-12 parts of toughening agent and 1-3 parts of compatibilizer, and the composite reinforcement was prepared by 4-vinyl-1-cyclohexene-1,2-epoxy, methyldiphenylsilane and toluene, and added to the PET material.

Benefits of technology

The pressure resistance, heat resistance and corrosion resistance of PET high-pressure resistant materials for aerosol bottles is significantly improved, ensuring that the material remains structurally intact at high temperatures and resists corrosion and pressure deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a PET high-pressure-resistant material for an aerosol bottle and a preparation method, and belongs to the technical field of preparation of high-pressure-resistant materials. The PET high-pressure-resistant material for the aerosol bottle is prepared from the following components in parts by weight: 60-80 parts of PET resin, 20-25 parts of nylon, 5-10 parts of a composite reinforcing agent, 4-9 parts of an anticorrosive agent, 7-12 parts of a toughening agent and 1-3 parts of a compatibilizer, the composite reinforcing agent is prepared from p-phenylenediacetic acid, 1, 4-cyclohexanedimethanol, isosorbide, pimelic acid and triphenyl phosphate, and the composite reinforcing agent is prepared from polyethylene glycol terephthalate. And the anti-corrosion agent is prepared from 4-vinyl-1-cyclohexene-1, 2-epoxy, methyl diphenyl silane and methylbenzene, and the anti-corrosion agent is prepared from the following components: the epoxy resin, the methyl diphenyl silane and the methylbenzene. The PET high-pressure-resistant material prepared by the method has excellent pressure resistance, heat resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure-resistant material preparation, and particularly relates to a PET high-pressure-resistant material for an aerosol bottle and a preparation method thereof. Background Art

[0002] Aerosol bottles are an important part of aerosols and the main body of aerosol pressure packaging. The choice of materials is crucial to the performance and safety of the product. PET (polyethylene terephthalate), as a high-performance polyester material, is widely used in packaging containers for cosmetics, toiletries, etc. due to its high transparency, good impact resistance, high temperature resistance and certain chemical resistance. Especially in recent years, with the improvement of environmental protection requirements and the development of new material technology, aerosol bottles made of PET have gradually emerged and the market demand has increased. In the application of aerosol bottles, pressure resistance is crucial. Since the inside of aerosol bottles is usually filled with a mixture of high-pressure gas and liquid, if the pressure resistance of the material is insufficient, the bottle will break and leak during transportation or use, which will not only damage the product, but also cause safety hazards to consumers. Therefore, the development of a high-pressure PET material is of great significance to the aerosol bottle industry.

[0003] Patent CN115160741B discloses a high-conductivity and high-strength PET composite material and a preparation method thereof, wherein the composite material comprises 60-90 parts of PET and 10-40 parts of calcium carbonate whiskers / spiral carbon fibers / PET masterbatch. The preparation method of calcium carbonate whiskers / spiral carbon fibers / PET masterbatch is to add polyaniline-modified calcium carbonate whiskers and polyaniline-modified spiral carbon fibers to ethylene glycol and stir evenly, add terephthalic acid and a catalyst and mix evenly, remove the material and pelletize it after vacuum high-temperature reaction to obtain calcium carbonate whiskers / spiral carbon fibers / PET masterbatch. By in-situ growing rod-shaped polyaniline on the surface of calcium carbonate whiskers and spiral carbon fibers, the dispersion of calcium carbonate whiskers and spiral carbon fibers in the PET matrix can be promoted, the cross-sectional bonding force can be enhanced, and the conductivity and mechanical strength of the PET mixed material can be improved. However, the heat resistance, pressure resistance and corrosion resistance of the PET material prepared by this method still have room for improvement. Summary of the invention

[0004] The object of the present invention is to provide a PET high pressure-resistant material for an aerosol bottle and a preparation method thereof, so as to solve the technical problem that the PET material prepared in the prior art has poor heat resistance, pressure resistance and corrosion resistance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The invention provides a PET high-pressure-resistant material for an aerosol bottle. The material is composed of the following components in parts by weight: 60-80 parts of PET resin, 20-25 parts of nylon, 5-10 parts of a composite reinforcing agent, 4-9 parts of an anticorrosive agent, 7-12 parts of a toughening agent, and 1-3 parts of a compatibilizer. The composite reinforcing agent is prepared from terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, pimelic acid and triphenyl phosphate, and the anticorrosive agent is prepared from 4-vinyl-1-cyclohexene-1,2-epoxy, methyl diphenyl silane and toluene.

[0006] Preferably, the method for preparing the composite reinforcing agent comprises the following steps: Q1: Add terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, tetrabutyl titanate and dimethyl tin oxide into a container, stir, introduce nitrogen, heat, increase the speed, continue to heat the reaction, and after the reaction is completed, obtain intermediate 1; Q2: Pimelic acid, 1,4-cyclohexanedimethanol, tetrabutyl titanate and dimethyltin oxide are added to a container, stirred, introduced with nitrogen, heated, increased the speed, and continued to heat the reaction. After the reaction is completed, intermediate 2 is obtained; Q3: Add intermediate 1, intermediate 2, antioxidant 1010, dimethyl tin oxide and triphenyl phosphate into a container, increase the temperature and reduce the pressure, stir at a low speed to obtain a crude product, dissolve, purify, and vacuum dry to obtain a composite reinforcing agent.

[0007] In the above process, the synthetic reaction formula of the composite reinforcing agent is as follows: Preferably, in Q1, the molar ratio of terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, tetrabutyl titanate and dimethyl tin oxide is (1-1.2): (0.51-0.85): (1.02-1.53): (0.006-0.007): (0.0005-0.0006), the stirring speed is 200-240 rpm, the nitrogen introduction time is 30-45 min, the heating temperature is 100-110 ° C, the speed is increased to 1000-1200 rpm, the temperature is raised to 250-260 ° C, and the reaction is carried out for 1-2 hours.

[0008] Preferably, in Q2, the molar ratio of pimelic acid, 1,4-cyclohexanedimethanol, tetrabutyl titanate and dimethyl tin oxide is (1-1.2): (0.9-1.3): (0.006-0.007): (0.0005-0.0006), the stirring speed is 200-220 rpm, the nitrogen introduction time is 30-45 min, the heating temperature is 90-100 ° C, the speed is increased to 800-1000 rpm, the temperature is raised to 180-190 ° C, and the reaction is carried out for 1-2 hours.

[0009] Preferably, in Q3, the amount ratio of intermediate 1, intermediate 2, antioxidant 1010, dimethyl tin oxide and triphenyl phosphate is (10-14) g: (10-13) g: (0.002-0.003) g: (0.001-0.002) g: (0.02-0.027) g, the temperature is raised to 260-270°C, the pressure is reduced to 0.2-0.4 mbar, the low-speed stirring speed is 30-45 rpm, the time is 5-8 h, and it is dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and the vacuum drying temperature is 50-55°C for 48-52 h.

[0010] Preferably, the method for preparing the anticorrosive agent comprises the following steps: S1: Add 4-vinyl-1-cyclohexene-1,2-epoxy, Karstedt catalyst and toluene into a container equipped with a reflux condenser, a thermometer and a stirrer, and stir to obtain an epoxy mixed solution; S2: Add methyldiphenylsilane to toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it, add the silane mixture dropwise, control the dropping speed, and after the addition is completed, keep warm for reaction. After the reaction is completed, perform rotary evaporation to obtain an anti-corrosion agent.

[0011] In the above process, 4-vinyl-1-cyclohexene-1,2-epoxy and methyldiphenylsilane are used as raw materials, and a hydrosilylation reaction is carried out under the catalysis of Karstedt catalyst to obtain an anticorrosive agent, wherein the synthesis reaction formula of the anticorrosive agent is as follows: The results of mass spectrometry analysis of the corrosion inhibitor were: m / z: 322.18 (100.0%), 323.18 (23.1%), 323.17(5.1%), 324.18 (3.9%), 324.17 (3.3%), 325.18 (1.0%).

[0012] Preferably, in S1, the usage ratio of 4-vinyl-1-cyclohexene-1,2-epoxide, Karstedt catalyst and toluene is (2.3-4.1) g: (0.2-0.3) g: (5-7.5) mL, and the stirring time is 30-45 min.

[0013] Preferably, in S2, the dosage ratio of methyldiphenylsilane and toluene is (5-8) g: (10-15) mL, heated to 80-85°C, the dropping speed is controlled to 2-3 drops / s, the insulation reaction temperature is 82-85°C, and the reaction time is 6-8h.

[0014] Preferably, the method for preparing the PET high pressure resistant material for aerosol bottles comprises the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0015] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention first uses terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, pimelic acid and triphenyl phosphate as raw materials to prepare a composite reinforcing agent, then uses 4-vinyl-1-cyclohexene-1,2-epoxy, methyldiphenylsilane and toluene as raw materials to prepare an anticorrosive agent, and the composite reinforcing agent and the anticorrosive agent are added to a PET material at the same time, so that the prepared PET high-pressure-resistant material for aerosol bottles has excellent pressure resistance, heat resistance and corrosion resistance.

[0016] 2. The present invention adds the prepared composite reinforcing agent to the PET high-pressure-resistant material for aerosol bottles, which can effectively improve its pressure resistance and heat resistance. The polymer chain in the composite reinforcing agent has high rigidity, and can build an effective support structure in the PET material to resist deformation. The cross-linked structure formed between some chain segments enhances the overall strength of the material, making it difficult to compress and deform. The strong interaction between the composite reinforcing agent and the PET matrix improves the bonding strength, effectively disperses and transfers stress, and enhances pressure resistance. The polymer chain of the composite reinforcing agent has high thermal stability, can maintain structural integrity at high temperatures, prevent PET from thermal decomposition and degradation, and can also reduce the risk of thermal stress concentration and damage at high temperatures, thereby significantly enhancing the heat resistance of the PET material.

[0017] 3. The present invention can effectively improve the corrosion resistance of PET high-pressure resistant material for aerosol bottles by adding the prepared anti-corrosion agent to the material. The silicon-oxygen bond and benzene ring structure contained in the anti-corrosion agent molecule have excellent chemical stability and can effectively resist the erosion of various corrosive substances. When added to the PET material, the anti-corrosion agent interacts with the PET molecular chain to form a dense protective film that is both stable and has a physical barrier effect, effectively isolating the penetration and diffusion of corrosive substances such as moisture, oxygen, acid and alkali, thereby improving the corrosion resistance of the PET material. DETAILED DESCRIPTION

[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1: This example discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 21.34 g of terephthalic acid, 9.36 mL of 1,4-cyclohexanedimethanol, 18.52 g of isosorbide, 0.221 mL of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction was completed, intermediate 1 was obtained; Q2: 1.76 g of heptanediol, 15.23 mL of 1,4-cyclohexanedimethanol, 0.094 g of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction, intermediate 2 was obtained; Q3: 12 g of intermediate 1, 11.5 g of intermediate 2, 0.002 g of antioxidant 1010, 0.001 g of dimethyl tin oxide and 0.023 g of triphenyl phosphate were added to a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After stirring at a low speed of 45 rpm for 8 hours, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and vacuum dried at 55°C for 52 hours to obtain a composite enhancer.

[0020] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 3.2 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.25 g of Karstedt catalyst and 6.25 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 6.5 g of methyldiphenylsilane to 12.5 mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8 hours. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0021] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 70 parts of PET resin, 22.5 parts of nylon, 7.5 parts of a composite reinforcing agent, 6.5 parts of an anticorrosive agent, 9.5 parts of a polyurethane resin, and 2 parts of POE-g-GMA.

[0022] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0023] Example 2: This example discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 19.4 g of terephthalic acid, 7.06 mL of 1,4-cyclohexanedimethanol, 14.89 g of isosorbide, 0.204 mL of tetrabutyl titanate and 0.009 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction was completed, intermediate 1 was obtained; Q2: 1.92 g of heptanediol, 12.46 mL of 1,4-cyclohexanedimethanol, 0.087 g of tetrabutyl titanate and 0.009 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction, intermediate 2 was obtained; Q3: 10 g of intermediate 1, 13 g of intermediate 2, 0.003 g of antioxidant 1010, 0.002 g of dimethyl tin oxide and 0.027 g of triphenyl phosphate were added to a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After stirring at a low speed of 45 rpm for 8 hours, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and vacuum dried at 55°C for 52 hours to obtain a composite enhancer.

[0024] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 2.3 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.3 g of Karstedt catalyst and 5 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 5g of methyldiphenylsilane to 15mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8h. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0025] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 60 parts of PET resin, 20 parts of nylon, 10 parts of a composite reinforcing agent, 9 parts of an anticorrosive agent, 7 parts of a polyurethane resin, and 3 parts of POE-g-GMA.

[0026] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0027] Embodiment 3: This embodiment discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 23.28 g of terephthalic acid, 11.77 mL of 1,4-cyclohexanedimethanol, 22.34 g of isosorbide, 0.238 mL of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction, intermediate 1 was obtained; Q2: 1.6 g of heptanediol, 18 mL of 1,4-cyclohexanedimethanol, 0.102 g of tetrabutyl titanate and 0.009 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction, intermediate 2 was obtained; Q3: 14 g of intermediate 1, 10 g of intermediate 2, 0.003 g of antioxidant 1010, 0.001 g of dimethyl tin oxide and 0.02 g of triphenyl phosphate were added to a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After low-speed stirring at 45 rpm for 8 h, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and vacuum dried at 55°C for 52 h to obtain a composite enhancer.

[0028] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 4.1 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.2 g of Karstedt catalyst and 7.5 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 8g of methyldiphenylsilane to 10mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8h. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0029] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 80 parts of PET resin, 25 parts of nylon, 5 parts of a composite reinforcing agent, 4 parts of an anticorrosive agent, 12 parts of a polyurethane resin, and 1 part of POE-g-GMA.

[0030] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0031] Embodiment 4: This embodiment discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 22.27 g of terephthalic acid, 8.12 mL of 1,4-cyclohexanedimethanol, 16.17 g of isosorbide, 0.217 mL of tetrabutyl titanate and 0.009 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction was completed, intermediate 1 was obtained; Q2: 1.83 g of heptanediol, 13.17 mL of 1,4-cyclohexanedimethanol, 0.099 g of tetrabutyl titanate and 0.009 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction was completed, intermediate 2 was obtained; Q3: 11 g of intermediate 1, 11 g of intermediate 2, 0.002 g of antioxidant 1010, 0.002 g of dimethyl tin oxide and 0.021 g of triphenyl phosphate were added into a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After stirring at a low speed of 45 rpm for 8 h, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added into methanol for purification, and vacuum dried at 55°C for 52 h to obtain a composite enhancer.

[0032] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 2.8 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.22 g of Karstedt catalyst and 5.5 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 6 g of methyldiphenylsilane to 11 mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8 hours. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0033] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 65 parts of PET resin, 21 parts of nylon, 8 parts of a composite reinforcing agent, 5 parts of an anticorrosive agent, 8 parts of a polyurethane resin, and 1.5 parts of POE-g-GMA.

[0034] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0035] Embodiment 5: This embodiment discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 20.13 g of terephthalic acid, 10.23 mL of 1,4-cyclohexanedimethanol, 20.58 g of isosorbide, 0.232 mL of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction, intermediate 1 was obtained; Q2: 1.65 g of heptanediol, 17.27 mL of 1,4-cyclohexanedimethanol, 0.089 g of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction, intermediate 2 was obtained; Q3: 13 g of intermediate 1, 12 g of intermediate 2, 0.002 g of antioxidant 1010, 0.002 g of dimethyl tin oxide and 0.025 g of triphenyl phosphate were added to a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After stirring at a low speed of 45 rpm for 8 hours, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and vacuum dried at 55°C for 52 hours to obtain a composite enhancer.

[0036] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 3.3 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.28 g of Karstedt catalyst and 6.5 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 7g of methyldiphenylsilane to 14mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8h. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0037] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 75 parts of PET resin, 23 parts of nylon, 6 parts of a composite reinforcing agent, 8 parts of an anticorrosive agent, 10 parts of a polyurethane resin, and 2.5 parts of POE-g-GMA.

[0038] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0039] Embodiment 6: This embodiment discloses a method for preparing a composite reinforcing agent, comprising the following steps: Q1: 21.12 g of terephthalic acid, 9.09 mL of 1,4-cyclohexanedimethanol, 19.32 g of isosorbide, 0.213 mL of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 240 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 1000 rpm, and the temperature was continued to rise to 260 ° C for 2 h. After the reaction was completed, intermediate 1 was obtained; Q2: 1.68 g of heptanediol, 14.27 mL of 1,4-cyclohexanedimethanol, 0.092 g of tetrabutyl titanate and 0.008 g of dimethyltin oxide were added to a container, stirred at 220 rpm, nitrogen was introduced for 45 min, heated to 100 ° C, the speed was increased to 800 rpm, and the temperature was continued to rise to 180 ° C for 2 h. After the reaction, intermediate 2 was obtained; Q3: 12 g of intermediate 1, 12 g of intermediate 2, 0.002 g of antioxidant 1010, 0.001 g of dimethyl tin oxide and 0.024 g of triphenyl phosphate were added to a container, the temperature was raised to 260°C and the pressure was reduced to 0.2 mbar. After stirring at a low speed of 45 rpm for 8 hours, a crude product was obtained. The crude product was dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and vacuum dried at 55°C for 52 hours to obtain a composite enhancer.

[0040] This embodiment discloses a method for preparing an anticorrosive agent, comprising the following steps: S1: 2.5 g of 4-vinyl-1-cyclohexene-1,2-epoxy, 0.24 g of Karstedt catalyst and 6.4 mL of toluene were added into a container equipped with a reflux condenser, a thermometer and a stirrer, and stirred for 45 min to obtain an epoxy mixed solution; S2: Add 5.5 g of methyldiphenylsilane to 13 mL of toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it to 80°C, add the silane mixture dropwise, and control the dropping speed to 2 drops / s. After the addition is completed, keep the reaction at 85°C for 8 hours. After the reaction is completed, rotary evaporate to obtain an anti-corrosion agent.

[0041] The present embodiment discloses a PET high pressure-resistant material for an aerosol bottle, which is composed of the following components in parts by weight: 72 parts of PET resin, 23.5 parts of nylon, 7 parts of a composite reinforcing agent, 7 parts of an anticorrosive agent, 11 parts of a polyurethane resin, and 1.9 parts of POE-g-GMA.

[0042] This embodiment discloses a method for preparing a PET high pressure resistant material for an aerosol bottle, comprising the following steps: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

[0043] Comparative Example 1: Compared with Example 1, in the process of preparing the composite reinforcing agent in Comparative Example 1, no terephthalic acid is added, and other conditions remain unchanged.

[0044] Comparative Example 2: Compared with Example 1, in the process of preparing the corrosion inhibitor in Comparative Example 2, 4-vinyl-1-cyclohexene-1,2-epoxy is not added, and other conditions remain unchanged.

[0045] Comparative Example 3: Compared with Example 1, in the process of preparing the PET high pressure-resistant material for aerosol bottles in Comparative Example 3, no composite reinforcing agent is added, and other conditions remain unchanged.

[0046] Comparative Example 4: Compared with Example 1, in Comparative Example 4, during the process of preparing the PET high pressure-resistant material for aerosol bottles, no anticorrosive agent is added, and other conditions remain unchanged.

[0047] Experimental example: According to GB / T 1040.1-2006, the tensile properties of the samples were tested. The samples were heated and the temperature at which the samples were deformed was recorded. The corrosion resistance of the samples was tested using 1 mol / L sodium hydroxide and 1 mol / L hydrochloric acid. The mass of the samples before and after the experiment was measured, and the corrosion rate was calculated. The test results are shown in the following table: Table 1 It can be seen from the test results in Table 1 that the PET high-pressure-resistant material for aerosol bottles prepared in Examples 1-6 of the present invention has excellent pressure resistance, heat resistance and corrosion resistance. By comparing Comparative Example 1 with Examples 1-6, it can be seen that the addition of terephthalic acid can effectively improve the pressure resistance and heat resistance of the PET high-pressure-resistant material for aerosol bottles; by comparing Comparative Example 2 with Examples 1-6, it can be seen that the addition of 4-vinyl-1-cyclohexene-1,2-epoxy can effectively improve the corrosion resistance of the PET high-pressure-resistant material for aerosol bottles; by comparing Comparative Example 3 with Examples 1-6, it can be seen that the addition of a composite reinforcing agent can effectively improve the pressure resistance and heat resistance of the PET high-pressure-resistant material for aerosol bottles; by comparing Comparative Example 4 with Examples 1-6, it can be seen that the addition of an anticorrosive agent can effectively improve the corrosion resistance of the PET high-pressure-resistant material for aerosol bottles.

[0048] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0049] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. PET high pressure resistant material for aerosol bottles, characterized in that: The invention is composed of the following components in parts by weight: 60-80 parts of PET resin, 20-25 parts of nylon, 5-10 parts of composite reinforcing agent, 4-9 parts of anticorrosive agent, 7-12 parts of toughening agent and 1-3 parts of compatibilizer, wherein the composite reinforcing agent is prepared from terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, pimelic acid and triphenyl phosphate, and the anticorrosive agent is prepared from 4-vinyl-1-cyclohexene-1,2-epoxy, methyl diphenyl silane and toluene.

2. The PET high pressure resistant material for aerosol bottles according to claim 1, characterized in that: The preparation method of the composite reinforcing agent comprises the following steps: Q1: Add terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, tetrabutyl titanate and dimethyl tin oxide into a container, stir, introduce nitrogen, heat, increase the speed, continue to heat the reaction, and after the reaction is completed, obtain intermediate 1; Q2: Pimelic acid, 1,4-cyclohexanedimethanol, tetrabutyl titanate and dimethyltin oxide are added to a container, stirred, introduced with nitrogen, heated, increased the speed, and continued to heat the reaction. After the reaction is completed, intermediate 2 is obtained; Q3: Add intermediate 1, intermediate 2, antioxidant 1010, dimethyl tin oxide and triphenyl phosphate into a container, increase the temperature and reduce the pressure, stir at a low speed to obtain a crude product, dissolve, purify, and vacuum dry to obtain a composite reinforcing agent.

3. The PET high pressure-resistant material for aerosol bottles according to claim 2, characterized in that: In Q1, the molar ratio of terephthalic acid, 1,4-cyclohexanedimethanol, isosorbide, tetrabutyl titanate and dimethyl tin oxide is (1-1.2): (0.51-0.85): (1.02-1.53): (0.006-0.007): (0.0005-0.0006), the stirring speed is 200-240 rpm, the nitrogen introduction time is 30-45 min, the heating temperature is 100-110°C, the speed is increased to 1000-1200 rpm, the temperature is raised to 250-260°C, and the reaction is carried out for 1-2 hours.

4. The PET high pressure-resistant material for aerosol bottles according to claim 2, characterized in that: In Q2, the molar ratio of pimelic acid, 1,4-cyclohexanedimethanol, tetrabutyl titanate and dimethyl tin oxide is (1-1.2): (0.9-1.3): (0.006-0.007): (0.0005-0.0006), the stirring speed is 200-220 rpm, the nitrogen introduction time is 30-45 min, the heating temperature is 90-100°C, the speed is increased to 800-1000 rpm, the temperature is raised to 180-190°C, and the reaction is carried out for 1-2 hours.

5. The PET high pressure-resistant material for aerosol bottles according to claim 2, characterized in that: In the Q3, the dosage ratio of intermediate 1, intermediate 2, antioxidant 1010, dimethyl tin oxide and triphenyl phosphate is (10-14) g: (10-13) g: (0.002-0.003) g: (0.001-0.002) g: (0.02-0.027) g, the temperature is raised to 260-270°C, the pressure is reduced to 0.2-0.4 mbar, the low-speed stirring speed is 30-45 rpm, the time is 5-8 h, and it is dissolved in a mixed solution of chloroform and trifluoroacetic acid in a volume ratio of 4:1, added to methanol for purification, and the vacuum drying temperature is 50-55°C for 48-52 h.

6. The PET high pressure-resistant material for aerosol bottles according to claim 1, characterized in that: The preparation method of the anticorrosive agent comprises the following steps: S1: Add 4-vinyl-1-cyclohexene-1,2-epoxy, Karstedt catalyst and toluene into a container equipped with a reflux condenser, a thermometer and a stirrer, and stir to obtain an epoxy mixed solution; S2: Add methyldiphenylsilane to toluene, stir evenly to obtain a silane mixture, and transfer it to a dropping funnel. Then install the dropping funnel in a container containing an epoxy mixed solution, heat it, add the silane mixture dropwise, control the dropping speed, and after the addition is completed, keep warm for reaction. After the reaction is completed, perform rotary evaporation to obtain an anti-corrosion agent.

7. The PET high pressure-resistant material for aerosol bottles according to claim 6, characterized in that: In the S1, the usage ratio of 4-vinyl-1-cyclohexene-1,2-epoxide, Karstedt catalyst and toluene is (2.3-4.1) g: (0.2-0.3) g: (5-7.5) mL, and the stirring time is 30-45 min.

8. The PET high pressure-resistant material for aerosol bottles according to claim 6, characterized in that: In the S2, the dosage ratio of methyldiphenylsilane and toluene is (5-8) g: (10-15) mL, heated to 80-85° C., the dropping speed is controlled to 2-3 drops / s, the heat-insulating reaction temperature is 82-85° C., and the reaction time is 6-8 h.

9. A method for preparing a PET high pressure resistant material for aerosol bottles according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: pre-mix PET resin, nylon, composite reinforcing agent, anticorrosive agent, toughening agent and compatibilizer, then add them into a stirring tank, and stir them thoroughly to obtain a mixture; Step 2: The mixed material is heated and melted, extruded, cooled, and solidified to obtain a PET high pressure-resistant material for an aerosol bottle.

Citation Information

Patent Citations

  • A high-conductivity, high-strength PET composite material and its preparation method

    CN115160741B

  • Reinforced modified PET polyester blend and polyethylene glycol terephthalate blend plastic

    CN112724610A

  • High and low temperature resistant modified PET material and preparation method thereof

    CN117165053A

  • High-strength polyester film and preparation method thereof

    CN117624851A

  • High-flame-retardant PET (Polyethylene Terephthalate) base film and preparation method thereof

    CN118221982A